New multilayered diamond/β-SiC composite architectures for high-performance hard coating. (15th January 2020) - Yuan, Ziyao; Guo, Yuning; Li, Cuihong; Liu, Lusheng; Yang, Bing; Song, Haozhe; Zhai, Zhaofeng; Lu, Zhigang; Li, Hong; Staedler, Thorsten; Huang, Nan; Jiang, Xin
Abstract: The design of the coating architecture plays an important role in improving the mechanical performance of the hard coating. In present work, several novel multilayered diamond/β-SiC composite architectures were deposited on cemented tungsten carbide substrates by hot filament chemical vapor deposition. Field emission scanning electron microscope (FE-SEM) observation reveals periodic multilayered configurations with diamond/β-SiC composite layers and microcrystalline diamond (MCD) or nanocrystalline diamond (NCD) layers. Moreover, Rockwell indentation, scratch and nano-indentation tests indicate that multilayered diamond/β-SiC composite and MCD coating possess not only good adhesion (52.9 ± 0.5 N) and crack propagation resistance, but also high hardness (83.6 ± 3.5 GPa) and modulus (856.1 ± 87.5 GPa) among all as-deposited coatings. For this configuration, the hardness of the coating is inherited from the MCD layer, while the low residual stress, enhanced adhesion and crack propagation resistance are due to the composite coating and multilayer architecture. Thus, the mechanical properties of diamond coating are improved by the innovative diamond/β-SiC composite multilayer, which provides a potential approach for high-performance diamond coated cutting tools. Graphical abstract: Image 1 Highlights: A new multilayered diamond/β-SiC composite coating with high hardness and sufficient adhesion is deposited. The innovative coating is consisted of periodic diamond/β-SiC composite and MCD multilayer as supporting layer. The relationship between the multilayered composite architectures and mechanical behaviors has been discussed in this work.